Acculturative Stress and Gang Involvement among Latinos: U.S.-born versus Immigrant Youth - Barrett, Alice N (2010)
Quantitative and qualitative data from the 2002 Latino Adolescent Transition Study were used to explore differences in acculturative stress and gang involvement between foreign-born and U.S.-born Latino middle school students. Regression analyses showed significant interactions between discrimination stress and immigration status as well as adaptation stress and immigration status. U.S.-born youths were significantly more likely to be gang-involved if they experienced discrimination stress. They were also less likely to be gang-involved if they experienced high adaptation stress. A minority of primarily foreign-born youths identified economic inequality and prejudicial attitudes as factors that differentiated them from Americans. Those reporting economic inequality were more likely to be gang-involved than those who did not. These findings suggest that the origins of gang involvement could differ between the two immigrant generations. Whereas U.S.-born Latinos may be more negatively affected by discrimination, foreign-born Latinos may be more sensitive to their comparatively low economic status